2012
DOI: 10.3329/jesnr.v5i1.11567
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Fine Rice Varieties as Influenced by Integrated Management of Poultry Manure Urea Super Granules and Prilled Urea

Abstract: Higher grain yield (2.45 t ha-1) was obtained in BRRI dhan34 than that of Kalizira (2.23 t ha-1). Fertilizer application @ 1.8g USG and other inorganic fertilizer ( full dose for T. aman + PM at 3.5 tha-1) gave the highest grain yield (2.85 t ha-1) and lowest grain yield (1.52 t ha-1) was found at control (no PM and NPKS). Grain yields were affected by the interaction of variety and nutrient management. The highest grain yield (2.88 t ha-1) was found in BRRI dhan34 coupled with 1.8g USG and other inorganic fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 1 publication
6
11
3
Order By: Relevance
“…The lowest grain yield (1.5 t ha -1 ) was produced by Kalijira (Figure 3). Similar results were found elsewhere (Islam et al, 2012;Tyeb et al, 2013), who reported that variety exerted variable effect on yield contributing characters and yield of rice. Differences in grain yield due to varieties were also reported by Yoshida (1994) and Siddeque et al (2002).…”
Section: Yieldsupporting
confidence: 91%
“…The lowest grain yield (1.5 t ha -1 ) was produced by Kalijira (Figure 3). Similar results were found elsewhere (Islam et al, 2012;Tyeb et al, 2013), who reported that variety exerted variable effect on yield contributing characters and yield of rice. Differences in grain yield due to varieties were also reported by Yoshida (1994) and Siddeque et al (2002).…”
Section: Yieldsupporting
confidence: 91%
“…The lowest grain yield was recorded in Bokuljoha (38.38 q ha -1 ) due to its small and fine grain quality. Similar results were found elsewhere (Tyeb et al, 2013;Islam et al, 2012), who reported that variety exerted variable effect on yield and yield contributing characters of rice. Bai et al (1992) reported that grain yield was found to be positively correlated with number of productive tillers hill -1 , number of grains panicle -1 both at genotypic and phenotypic level.…”
Section: Grain Yield (Q Ha -1 )supporting
confidence: 91%
“…Tyeb et al 2013; Islam et al (2012) reported that variety exerted variable effect on yield contributing characters of rice. The difference in variety showed significant difference in number of grains panicle -1 typically due to the difference in genetic material.…”
Section: No Of Grains Panicle -1mentioning
confidence: 99%
“…These findings suggested that average 60 kg of urea could be saved by using USG over PU. Islam et al, (2012) demonstrated that deep placement of USG could be a profitable N management technique. They also found that grain yield with only 55 kg N ha -1 in USG form as against 80 kg N ha -1 in the form of prilled urea was same.…”
Section: Deep Placement Of Usg In Bed Saved N Fertilizer Consumption mentioning
confidence: 99%